Transport of Lipophilic Anti‐Tuberculosis Drug Benzothiazone‐043 in Ca3(PO4)2 Nanocontainers. Issue 1 (27th November 2020) - Rudolph, David; Redinger, Natalja; Schaible, Ulrich E.; Feldmann, Claus
Abstract: 1, 3‐Benzothiazin‐4‐one‐043 (BTZ043) is a novel anti‐mycobacterial agent for tuberculosis (TB) therapy with highly hydrophobic properties. In order to enhance local drug concentrations by improved administration and delivery to the site of the mycobacterial infection, we suggest BTZ043/Toc@Ca(ds)2 @Ca3 (PO4 )2 nanocontainers made via a microemulsion approach for drug delivery (Toc: tocopherol; ds: dodecylsulfate). Based on our concept, the surfactant of the microemulsion itself is used to stabilize the droplet phase by interaction with Ca 2+, followed by the formation of an inorganic Ca3 (PO4 )2 sphere wall in one‐pot reaction. Tocopherol (vitamin E) was used as biocompatible droplet phase of the microemulsion to dissolve the highly lipophilic BTZ043. According to electron microscopy and electron spectroscopy, the resulting BTZ043/Toc@Ca(ds)2 @Ca3 (PO4 )2 nanocontainers exhibit an outer diameter of 28±8 nm and a sphere wall of 4±1 nm. The inner cavity, 18±7 nm in diameter, is loaded with BTZ043 with a concentration of 30.5 μg/mL. First in vitro tests with murine bone marrow derived macrophages infected with Mycobacterium tuberculosis show promising antibiotic activity of the BTZ043/Toc@Ca(ds)2 @Ca3 (PO4 )2 nanocontainers. Abstract : 1, 3‐Benzothiazin‐4‐one‐043 is a new anti‐mycobacterial agent for tuberculosis (TB) therapy with highly hydrophobic properties. To increase local drug concentrations by improved administration and delivery to the site of the mycobacterial infection, the use of BTZ043/Toc@Ca(ds)2 @Ca3 (PO4 )2 nanocontainers made via a microemulsion approach for drug delivery is suggested (Toc: tocopherol; ds: dodecylsulfate).